Synthesis and characterization of carbon quantum dots derived from green precursor for metal sensing and photodegradation of 2,4-dichlorophenol - Tai, Jun Yan (2019)
The contamination of heavy metal and endocrine disrupting chemicals (EDCs) in water bodies had raised serious health and environmental concerns. Therefore, the development of green materials for heavy metal sensing and EDCs degradation was needed for safer water supply. This work highlights on the development of carbon quantum dots (CQDs) using human fingernails (FNCQDs) and Arabian dates (AD-CQDs) for metal sensing application. The CQDs were at different loadings on graphitic carbon nitride (g-C3N4) using hydrothermal method for photodegradation of 2,4-dichlorophenol (2,4-DCP) under sunlight irradiation. The FN-CQDs (5.60 nm) and AD-CQDs (4.79 nm) improved visible light harvesting property and charge carrier lifetime upon incorporation with g-C3N4. In metal sensing experiments, the FN-CQDs were more selective towards the detection of Cu2+ ions while AD-CQDs were more selective towards detection of Fe3+ ions. Both CQDs were sensitive to heavy metal at 1 nM. Both of FN-CQDs loaded with 50 wt% g-C3N4 (FN-CQDs/gC3N4(50)) and AD-CQDs loaded with 20 wt% g-C3N4 (AD-CQDs/g-C3N4(20)) achieved the highest degradation rate of 2,4-DCP which was 2.64 and 3.15 times higher than that of pure g-C3N4. Regardless of the precursor type (fingernails or Arabian dates), the photocatalytic performance in lower (10, 15, 20, 30 wt%) and higher (40, 50 wt%) amount of CQDs was mainly influenced by charge carrier lifetime and visible light absorption, respectively. FN-CQDs/g-C3N4(50) fully degraded 2,4-DCP 15 min faster than that of AD-CQDs/g-C3N4(20). However, AD-CQDs were preferably chosen to improve g-C3N4 because lower amount of CQDs could achieve similar level of performance with lower production cost.